Carotid atherosclerosis, vascular risk factors and relation to cognitive test results : the Tromsø study 1994-2008. - Arntzen, Kjell Arne (University of Tromsø, 2012)
The papers of this thesis are not available in Munin: 1. Arntzen KA, Schirmer H, Wilsgaard T, Mathiesen EB.: 'Impact of cardiovascular risk factors on cognitive function : the Tromsø Study', European Journal of Neurology (2011), 18(5):737–743. Available at http://dx.doi.org/10.1111/j.1468-1331.2010.03263.x 2. Arntzen KA, Schirmer H, Johnsen SH, Wilsgaard T, Mathiesen EB.: 'Carotid atherosclerosis predicts lower cognitive test results : a 7 years follow-up study in 4371 stroke-free subjects. The Tromsø Study', Cerebrovascular Diseases (2012), 33(2):159-165, and available at http://dx.doi.org/10.1159/000334182 3. Arntzen KA, Schirmer H, Johnsen SH, Wilsgaard T, Mathiesen EB.: 'Carotid artery plaque progression and cognitive decline. The Tromsø Study 1994- 2008'. Accepted manuscript. Published in European Journal of Neurology, Volume 19, Issue 10, October 2012. Available at http://dx.doi.org/10.1111/j.1468-1331.2012.03728.x The prevalence of dementia and cognitive impairment is rising worldwide as the number of elderly people increases in most countries. Vascular risk factors and carotid artery atherosclerosis have in some epidemiological studies been associated with increased risk of cognitive decline. The carotid artery is essential for blood supply to the brain, but is also vulnerable to atherosclerosis. The degree of atherosclerosis in the carotid artery can easily be measured by ultrasonography. The population-based Tromsø study, with repeated screening surveys of the Tromsø population, has made it possible to follow participants prospectively. Repeated carotid ultrasound scanning and cognitive test assessments have provided a unique opportunity for assessing change in atherosclerosis and change in cognitive test scores. In this study we assessed the impact of different vascular risk factors on scores in three cognitive tests after 7 years of follow-up, and studied if carotid atherosclerosis and progression of atherosclerosis were independent risk factors for lower cognitive test scores and cognitive decline ...